Primary and Secondary Influencing Agents on Gastropod Populations of Three Habitats in Washington State - L. Daniel Myers (Hello World!, 1972)
The effects of the micro-environment upon the population size of snails has for many years been recognized by malacologists. Accordingly, an attempt has been made to determine the primary and secondary limiting factors which influence the numbers of gastropods within specific areas.